Information Support of Monitoring as a Tool of Ecological Optimization of Agricultural Land Use - BAKINOVA, Tatiana Ivanovna; DARBAKOVA, Natalia Evgenievna; KAZAKOVA, Gerenzel Yashkulovna; SANGADZHIEVA, Saglara Alexandrovna; DARBAKOVA, Irina Evgenievna (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.10.1(33).19, 2019)
The purpose of the present work is to analyze the features of negative processes occurring in the land fund of the Republic of Kalmykia, to substantiate the organizational measures aimed at providing information support of monitoring as a tool for environmental optimization of the territory. Methods. The authors used general scientific methods, such as comparison, generalization, analysis, synthesis, as well as particular scientific methods, which included statistical, field, cartographic, and expert evaluation methods. The use of these methods made it possible to carry out ecological and geographical, environmental analysis of the territory, as well as to assess the adverse anthropogenic effects. Regional studies with regard to the degradation processes, their rates and intensity allowed justifying the choice of model polygons in different areas of Kalmykia. Model polygons will serve the basis for the data generation for the information database in order to predict the development of certain processes, as well as identify positive and negative trends.